Effects of Supportive Therapy on Mothers in Provision of Energy And Protein Intake to Toddlers with Stunting Risk - Yuli Lestari; Richta Puspita Haryanti; Ida Subardiah Pelitawati (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
The main problem of nutrition in developing countries is nutritional problems that occur in children. The incidence of high-risk stunting that occurs in this age range is a transition period from complementary feeding where inadequate complementary feeding practices result in inadequate intake of nutrients so that they are susceptible to infectious diseases that trigger nutritional problems. This study aims to know the effect of supportive therapy to mothers in providing energy and protein food intake for toddlers with risk of stunting. The research design used a pre-experimental design (one-group pre-post test design). The total sample of 34 respondents was selected using a consecutive sampling technique. The intervention was given supportive therapy according to the stages and action sessions.The results showed that there was a change in the mean score of stunting risk management between before (43.79) and after (54.03) being given supportive therapy. The p-value = 0.000 means that there is an effect of supportive therapy on the management of stunting risk in mothers with stunting risk of toddlers. Supportive therapy is known to be effective in changing maternal behavior in managing stunting risk. Supportive therapy carried out continuously will change the mother's attitude.